The Influence of Picture Card Learning Media on Arabic Speaking Skills: A True Experimental Study - Khoirunnisa, Khoirunnisa; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the influence of picture card learning media on Arabic speaking skills and determine the significance and correlation between them among seventh-grade female students at the Integrated Islamic Junior High School Darul Fikri in Sidoarjo. The research employed a quantitative approach with a True Experimental design. The collected data were analyzed using correlation analysis. The findings indicated that the average score for Arabic speaking skills in the experimental group was 82.15, falling under the